Life in the Camps: Prince of Wales Island, 1980-1996 - Reilly, Marili Green; United States. Federal Highway Administration. Western Federal Lands Highway Division
Approximately 30 years after Western Federal Lands Highway Division became involved in road improvement projects on the Prince of Wales Island, the road system was recognized as an Alaska Scenic Byway. In commemoration of this event, WFLHD retirees and employees were invited to share their memories of work on the island.